Methane emissions and carbon storage from household paper disposal in Brazil during 1901-2016 - Sanquetta, Carlos Roberto; Dalla Corte, Ana Paula; Sanquetta, Mateus Niroh Inoue; Maas, Greyce Charllyne Benedet; Tomé, Margarida (Desenvolvimento e Meio Ambiente, 2022)
In this paper, we estimated the methane emissions by the disposal of sanitary and domestic-use paper consumed throughout Brazil from 1901 to 2016. The apparent consumption of this type of paper from 1961 to 2016, calculated from the data of the FAOSTAT system, was used to estimate the amount of waste disposed of annually in three site categories: sanitary landfill, controlled dump, and open-air, uncontrolled dump. The 2006 IPCC Guide methodology was used to calculate CH4emissions and long-term carbon storage. Nine scenarios based upon the law that establishes the National Solid Waste Policy (NSWP) were examined, considering 100% waste disposal and treatment in landfills or incineration from 2014. The total emission was estimated at 1.967 MtCH4, corresponding to 55.080 MtCO2eq by GWP-AR5, and the stored carbon at 3.724 Mt, corresponding to 13.655 MtCO2eq. CH4emission increased beyond the population growth rate due to an increase in the per capita paper consumption in the country, from 0.02 kgCH4.year-1 in 1961 to 0.30 kg CH4.year-1 in 2016. The NSWP has not yet been accomplished, and the scenarios outlined indicate that, from the point of view of CH4 emissions, it would be more advantageous to carry out incineration instead of applying other waste treatment technologies.